Association of Extreme Nocturnal Dipping With Cardiovascular Events Strongly Depends on Age. Issue 2 (February 2020) - Palatini, Paolo; Verdecchia, Paolo; Beilin, Lawrence J.; Eguchi, Kazuo; Imai, Yutaka; Kario, Kazuomi; Ohkubo, Takayoshi; Pierdomenico, Sante D.; Saladini, Francesca; Schwartz, Joseph E.; Wing, Lindon; Signorotti, Sara; et al.
Abstract : Whether extreme dipping is associated with cardiovascular events (CVE) is unclear. The present study was conducted to test the hypothesis that the prognostic role of extreme dipping varies as a function of age. The analysis was performed in 10 868 participants (53% men) aged 53±15 (mean±SD) years enrolled in 8 prospective studies. Using the ambulatory systolic blood pressure nocturnal decline, we identified 4 groups: dippers (>10%–20%), nondippers (>0%–10%), reverse dippers (⩽0%), and extreme dippers (>20%). The association between dipping category and CVE was estimated as a function of age using Cox models adjusted for sex, average 24-hour systolic blood pressure, and traditional risk factors. During a median follow-up of 5.7 years, there were a total of 829 CVE (168 fatal). For extreme dippers, no increase in risk of CVE was observed among the participants <70 years (hazard ratio, 0.99 [95% CI, 0.73–1.34]; P =0.93) compared with dippers. In contrast, among the participants ≥70 years, there was a significant increase in risk (hazard ratio, 1.88 [95% CI, 1.14–3.11]; P =0.013). Among the octogenarians, the hazard ratio (95% CI) for CVE were 2.34 (1.12–4.93) for nondippers ( P =0.024), 3.91 (1.75–8.73) for reverse dippers ( P =0.001), and 4.12 (1.64–10.37) for extreme dippers ( P =0.003) compared with dippers. These data show that extreme dipping is not associated with poorer outcome in people younger than 70 years. A U-shaped relationship between nocturnal blood pressure dipping and adverse outcome is present in subjects older than 70 years. In the octogenarian extreme dippers, the risk of CVEs was 4× higher than in the dippers and similar to that in the reverse dippers. Abstract : Supplemental Digital Content is available in the text.